(untitled) (Perner’s Contacts, 2012)
Adoption of the “Directive of the European Parliament and of the European Council No. 2008/96/EC on road infrastructure safety management" (29) brought a new impetus to road traffic safety evaluation. The consequent Czech Act No. 152/2011 Coll. on roads obliges their operators to evaluate the traffic safety on a regular basis. It brings a new challenge – evaluation of road safety using traffic conflict analysis techniques and performance measurement. This paper follows the article (28) published earlier.